Thrombomodulin is essential for maintaining quiescence in vascular endothelial cells - Giri, Hemant; Panicker, Sumith R; Cai, Xiaofeng; Biswas, Indranil; Weiler, Hartmut; Rezaie, Alireza R (Proceedings of the National Academy of Sciences - PNAS, 2021)
Thrombomodulin (TM) is a thrombin receptor on endothelial cells that is involved in promoting activation of the anticoagulant protein C pathway during blood coagulation. TM also exerts protective anti-inflammatory properties through a poorly understood mechanism. In this study, we investigated the importance of TM signaling to cellular functions by deleting it from endothelial cells by CRISPR-Cas9 technology and analyzed the resultant phenotype of TM-deficient ( ) cells. Deficiency of TM in endothelial cells resulted in increased basal permeability and hyperpermeability when stimulated by thrombin and TNF-α. The loss of the basal barrier permeability function was accompanied by increased tyrosine phosphorylation of VE-cadherin and reduced polymerization of F-actin filaments at cellular junctions. A significant increase in basal NF-κB signaling and expression of inflammatory cell adhesion molecules was observed in cells that resulted in enhanced adhesion of leukocytes to cells in flow chamber experiments. There was also a marked increase in expression, storage, and release of the von Willebrand factor (VWF) and decreased storage and release of angiopoietin-2 in cells. In a flow chamber assay, isolated platelets adhered to cells, forming characteristic VWF-platelet strings. Increased VWF levels and inflammatory foci were also observed in the lungs of tamoxifen-treated ERcre-TM mice. Reexpression of the TM construct in cells, but not treatment with soluble TM, normalized the cellular phenotype. Based on these results, we postulate cell-bound TM endows a quiescent cellular phenotype by tightly regulating expression of procoagulant, proinflammatory, and angiogenic molecules in vascular endothelial cells.